Fuzzy sets in distributed traffic control - Nakamiti, G. [UNESP]; Gomide, F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1996)
The task of controlling urban traffic requires flexibility, adaptability and handling uncertain information spread through the intersection network. The use of fuzzy sets concepts convey these characteristics to improve system performance. This paper reviews a distributed traffic control system built upon a fuzzy distributed architecture previously developed by the authors. The emphasis of the paper is on the application of the system to control part of Campinas downtown area. Simulation experiments considering several traffic scenarios were performed to verify the capabilities of the system in controlling a set of coupled intersections. The performance of the proposed system is compared with conventional traffic control strategies under the same scenarios. The results obtained show that the distributed traffic control system outperforms conventional systems as far as average queues, average delay and maximum delay measures are concerned.
Keywords: Distributed parameter control systems; Fuzzy sets; Traffic control; Urban traffic; Fuzzy control